1992
DOI: 10.1093/nar/20.2.237
|View full text |Cite
|
Sign up to set email alerts
|

The LCR-like α-globin positive regulatory element functions as an enhancer in transiently transfected cells during erythroid differentiation

Abstract: A positive regulatory element (PRE) similar to the locus control region (LCR) of the human beta-globin gene cluster has recently been identified 40 kb upstream of the human zeta-globin mRNA cap site (Higgs D.R. W.G. Wood, A.P. Jarman, J. Sharpe, J. Lida, I.M. Pretorius, and H. Ayyub. 1990). We investigated the influence of the alpha PRE on human alpha-globin promoter activity in transiently transfected cells. The introduction of the alpha PRE into alpha-globin promoter/CAT expression constructs increased alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
3

Year Published

1992
1992
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 30 publications
2
30
0
3
Order By: Relevance
“…pA and poly A, polyadenylation site; ex1 to ex3, exon 1 to exon 3. was found to confer a strong (ϳ30-fold) positive effect on expression, which shows that this rabbit ␣-globin 5Ј flanking DNA segment is capable of responding to an enhancer. This result is consistent with the results of earlier studies with human ␣-globin gene constructs (31,36,47). In the test shown in Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…pA and poly A, polyadenylation site; ex1 to ex3, exon 1 to exon 3. was found to confer a strong (ϳ30-fold) positive effect on expression, which shows that this rabbit ␣-globin 5Ј flanking DNA segment is capable of responding to an enhancer. This result is consistent with the results of earlier studies with human ␣-globin gene constructs (31,36,47). In the test shown in Fig.…”
Section: Resultssupporting
confidence: 93%
“…1). Furthermore, reporter gene constructs promoted by the 5Ј flanking sequences of the ␣-globin gene that do show enhanced expression in the presence of HS Ϫ40 do not contain internal ␣-globin gene sequences (31,36), consistent with a role for internal sequences in enhancer-independent expression. Several possible explanations exist for the activity of this intragenic region.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Further remodeling and modification of the chromatin structure must occur in erythroid cells, however, since several new HS sites appear, including those at the HS-40 element and the promoter regions of the -and ␣-globin genes (54, 59). These latter sites apparently result from erythroid lineage-specific binding of nuclear factors to the above transcriptional regulatory elements, as demonstrated by previous genomic footprint analysis of 60) and of the ␣-globin upstream promoters (47).HS-40 acts as a classical enhancer in transient transfection assays (44,46,60), and it confers appropriate developmental control of the human -globin promoter activity in transgenic mice (19,23,45,56). In vitro and in vivo binding studies have shown that the HS-40 enhanceosome consists mainly of six DNA sequence motifs that are bound with nuclear factors in an erythroid lineage-specific manner: two NF-E2/AP1 motifs (5Ј-NA and 3Ј-NA), three GATA-1 motifs (b, c, and d), and a GT motif (26,50,60) (Fig.…”
mentioning
confidence: 73%
“…Circulating blood cells from day 10.5 (d10.5) yolk sacs were isolated in phosphate-buffered saline and stained as described. 30,31 In all experiments, multiple embryos (Ͼ 10) were analyzed at each stage for each transgenic line. Analysis of wild type and each mutant line with Fisher exact test gives values between 0.061 and 0.098.…”
mentioning
confidence: 99%